Evolution of α-synuclein conformation ensemble toward amyloid fibril via liquid-liquid phase separation (LLPS) as investigated by dynamic nuclear polarization-enhanced solid-state MAS NMR. (July 2022) - Takamuku, Mika; Sugishita, Tomoaki; Tamaki, Hajime; Dong, Lingyingzi; So, Masatomo; Fujiwara, Toshimichi; Matsuki, Yoh
Abstract: Protein fibrillation and human neurodegenerative diseases, with a profound underlying connection suggested between them, have been the subject of intense investigations in the medical, biophysical and bio-engineering sciences. For gaining the molecular mechanistic insights into such connection, i.e., the cause and effect, atomic-resolution molecular structure information especially on the initial oligomeric states is of paramount importance, not only that on the mature amyloid fibrils. α -Synuclein ( α Syn) and its amyloid fibril has a direct relevance to the Parkinson's disease and other synucleinopathies, but what triggers the fibrillation is still not entirely clear. We here describe the liquid-liquid phase separation (LLPS) of α Syn and investigate its conformational evolution from its monomeric state into oligomer state within the early-stage of the phase-separated droplets, mainly using solution and magic-angle spinning (MAS) solid-state nuclear magnetic resonance (NMR) spectroscopies, aided with optical and fluorescent microscopies and CD spectroscopy. Based on the analysis of the intricately broadened shapes of the MAS NMR peaks observed for isotopically 13 C-labeled His-50 of α Syn, we show that the distribution of the α Syn conformation is skewed from the initial completely random state to a loose β -rich ensembles at/around His-50 as early as day-3 (d3) within the droplet. This intra-droplet loose β -rich assembly showed a very slow progression until d8, and eventually maturated into ThT-positive, long and unbranched amyloid fibrils after 8 weeks. The obtained information on the evolution of the distribution of the conformation ensemble is unique, and difficult to obtain with X-ray crystallography and cryo-electron microscopy (cryoEM). In particular, the sensitivity-enhanced MAS NMR based on the low-temperature dynamic nuclear polarization (DNP) technique was proven to be a key tool in characterizing the conformational ensemble with dilute protein samples such as the liquid-phase droplets. Highlights: α -Synuclein forms phase-separated liquid droplets in molecular crowding condition. Evolution of conformational ensemble within early-stage droplet was studied. Auto-inhibitory form of α Syn is released upon droplet formation. α Syn forms a loose β -rich assembly in the droplet that grows into amyloid fibrils. Dynamic nuclear polarization-enhanced solid-state NMR is a key tool for such study.